Effects of Ordering Resistance and Aerobic Exercise Sequence on Energy Expenditure - Woldt, J. M.; Beltz, N. M.; Clark, D. J.; St. Mary, J. K.; Tilque, J. D. (My University, 2010)
There has been little research to determine the optimal order of aerobic and resistance exercise with respect to the amount of calories expended, which may provide a rationale for considering the sequence of exercise when designing exercise programs. Our experiment was designed to examine the effects of exercise sequence on energy expenditure during a single exercise bout.
Color poster with text, table, and graphs.
Keywords: Exercise--Planning; Aerobic exercises--Physiological aspects; Isometric exercise--Physiological aspects; Energy metabolism; Posters